Microstrip Inset Fed Rectangular Dielectric Resonator Antenna for Near Field Communication - Bahbaswata Mohapatra, Sovan Mohanty, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the availability of only limited dimensions of dielectric material, frequency tuning is very challenging in a dielectric resonator antenna. The objective is to enhance the tunability range of the DRA by altering the inductive inset feeding techniques. In this paper, novel low-profile rectangular dielectric resonator antennas with three different microstrip inset feeding mechanisms are studied and analyzed. It is observed that by varying the feeding techniques, the operating frequency can be easily altered, without significant variation in the impedance match. The dielectric waveguide model is used for approximate calculation of the dimension, and magnetic wall modelling is used for the overall analysis. The reflection coefficient, radiation pattern, co and cross-polarization, and gain are studied. The proposed antenna is resonating in the upper spectrum of the X band, and the lower spectrum of the Ku band with efficiency as high as 99%, a gain of 7 dBi, and the output pattern shows a broadside mode.